Akira. Book two - Ōtomo, Katsuhiro, 1954- (Kodansha Comics, 2010)
Despite being stuck in a frozen status, Akira still poses a threat to Neo-Tokyo and Tetsuo might be the city's only hope if it is ever released, but Tetsuo and his powers have become unstable and a group gathers to stop him from doing the unthinkable.